2022
DOI: 10.1002/ijop.12840
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, narcissism and social anxiety in relation to social media and internet addiction symptoms

Abstract: There has been considerable interest in trait correlates of excessive or problematic use of the internet, known as internet addiction. However, the concept of internet addiction has been criticised as too broad. Specific forms of excessive internet use, for example, social media, may have different trait correlates compared to internet use in general. The present study compared levels of internet and social media addiction symptoms in relation to three traits previously linked to one or the other form of exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In this study, we focused on the youngsters' Facebook users. The total data was 1473 posts of style themes (Colman, 2009) with sub-theme namely; appearance (Griffiths et al, 2018), identity (Yang et al, 2022Zinn et al, 2022), and Narcissistic subtheme (Lyvers et al, 2022). In analyzing the data that have been classified based on the themes, subthemes, and spectrums, we utilized AntConc application to prove and interpret the lexical issues found in each theme (Isam, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focused on the youngsters' Facebook users. The total data was 1473 posts of style themes (Colman, 2009) with sub-theme namely; appearance (Griffiths et al, 2018), identity (Yang et al, 2022Zinn et al, 2022), and Narcissistic subtheme (Lyvers et al, 2022). In analyzing the data that have been classified based on the themes, subthemes, and spectrums, we utilized AntConc application to prove and interpret the lexical issues found in each theme (Isam, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Teenagers with narcissistic behavior tend to pride themselves and show off in public (Casale & Banchi, 2020;Errasti et al, 2017;McCain & Campbell, 2018). In line with the abundance of social media access, the tendency of adolescents to show this attitude through social media so as to get recognition from others (Lyvers et al, 2022). There is a spectrum or dominant topic at the core of this subtheme which manifests the main issue involving the spectrum of physical visualization.…”
Section: Narcissistic Subthemementioning
confidence: 99%
“…Indeed, many studies on social media showed that FOMO is related to depression [136] and mental wellbeing [127]. At the same time, Narcissism appeared to be a driver of Internet and social media addiction [137].…”
Section: Human Behavior and Emerging Technologiesmentioning
confidence: 99%
“…A recent study has shown an association between problematic SNS use and eating disorder that was mediated by muscle dysmorphia ( 26 ). Problematic SNS use symptoms correlated with anxiety and narcissism ( 27 , 28 ). Finally, problematic SNS use may place individuals at risk for potentially problematic drinking ( 29 ).…”
Section: Comorbidity With Other Disordersmentioning
confidence: 99%